S136 Mtor Signalling Is An Essential Pathway For Tgf-β1 Induced αsma And Collagen Gene Expression. (10th November 2014) - Woodcock, HV; Peace, S; Nanthakumar, CB; Maher, TM; Mercer, PF; Chambers, RC
Abstract : Emerging evidence suggests a role for PI3K/mTOR signalling in the pathology of organ fibrosis. The aim of this study was to delineate PI3K/mTOR signalling in response to TGF-β1 stimulation of primary human lung fibroblasts (HLFs), and to investigate the role of this pathway in TGF-β1 mediated myofibroblast differentiation and collagen synthesis. A time-course of SMAD 2/3 and Akt (Ser473) phosphorylation, the major downstream effector of the PI3K/mTOR pathway, was constructed to assess TGF-β1 induced signalling kinetics in HLFs. TGF-β1 (1 ng/ml) induced rapid phosphorylation of SMAD2/3, peaking at 1 h, followed by Akt phosphorylation which peaked 12 h after initial stimulation. Maximal expression of ACTA2 and COL1A1 was observed 36 h after TGF-β1 stimulation, correlating with the delayed time-course of Akt phosphorylation. To investigate the role of the PI3K/mTOR pathway in TGF-β1 induced myofibroblast differentiation and collagen gene expression, HLFs were treated with pharmacological titrations of potent pathway inhibitors. Maximal Akt signalling and expression of ACTA2 and COL1A1 were significantly inhibited by a dual PI3K/mTOR inhibitor, while SMAD phosphorylation was unaffected. Treatment with an ATP competitive mTOR inhibitor also resulted in significantly reduced Akt phosphorylation and expression of ACTA2 and COL1A1, in response to TGF-β1 . In contrast, treatment of HLFs with either an allosteric or ATP competitive Akt inhibitor showed no inhibitory effect on TGF-β1 induced gene expression. These data suggest PI3 kinase/mTOR signalling is an important component in TGF-β1 induced αSMA and collagen gene expression and that an mTOR dependent, Akt independent pathway mediates this functional response in primary HLFs.